On Fermi-Walker transformation for timelike flows in spacetime - Korpinar, Talat; Baleanu, Dumitru; Korpinar, Zeliha; İnç, Mustafa (Elsevier, 2021)
In this manuscript, we firstly suggest different type for Fermi-Walker transportations along with flow lines of a non-vanishing vector field in Minkowski spacetime. Moreover, we construct the evolution equations of Frenet fields by Fermi-Walker derivative in Minkowski spacetime. Also, Fermi Walker parallelism is obtained the evolution equations of Frenet fields. Finally, we obtain some new results for flows by this new derivative in Minkowski spacetime. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Fluid flow; Fermi-Walker transport; Minkowski spacetime